AKTIVITAS ANTIHIPERGLIKEMIA FRAKSI ETIL ASETAT DAUN SALAM (Syzygium polyanthum) TERHADAP TIKUS PUTIH YANG DIINDUKSI ALOKSAN MONOHIDRAT - Prambudi, Dhimas Toni Angger; Meles, Dewa Ketut; Widiyatno, Thomas Valentinus (JURNAL KAJIAN VETERINER, 2022)
Bay leaf (Syzygium polyanthum) is traditionally used for diabetes treatment in Indonesia. It’s contains antioxidant that prevent the free radicals due to hyperglycemic condition. The purpose of this study is to demonstrate the ability of the ethyl acetate fraction of bay leaf in male white rats had hyperglycemia due to alloxan administration. This study used laboratory tests in which up to 24 white rats were randomly separated into six groups. Intraperitoneal administration of alloxan at a dose of 170 mg/Kgbw is used to induce hyperglycemia. A group of healthy rats (K-) were administered 0,5% CMC Na suspension 1mL/day. A group of hyperglycemic rats (K+) received metformin at a dose of 45 mg/Kgbw/1mL/day, while a group of hyperglycemic rats (P0) received 0.5% CMC Na suspension at a dose of 1mL/day. Three hyperglycemia treatment groups received different amounts of ethyl acetate fraction of bay leaf for 14 days. The P1 group received 125 mg/Kgbw/1mL/day of bay leaf ethyl acetate fraction extract, the P2 group received 250 mg/Kgbw/1mL/day, and the P3 group received 500 mg/Kgbw/1mL/day. Blood glucose levels were measured before and after alloxan administration, and then again on day 14. After 14 days of treatment, all rats were euthanized, and blood from the heart was collected to examine the insulin levels. To determine the differences between treatments, statistical analysis utilizing ANOVA was used, followed by Duncan's test. The findings revealed administered an ethyl acetate fraction of bay leaf can lower blood glucose and increased insulin levels in rats had hyperglycemia.